Tunnel diode integrated two-layer microstrip patch antenna - Srivastava S.; Vishvakarma B.R. (My University, 2025)
Theoretical investigations were carried out on the GaAs and Ge tunnel-diode-loaded patch with one parasitic element. It has been found that the radiated power increases due to mutual coupling between the patches typically by 1.95 dB in case of GaAs tunnel-diode-loaded patch and 5.95 dB in case of Ge tunnel-diode-loaded patch. It is also observed that the antenna can be operated over a range of frequency from 0.9975 GHz to 1.0002 GHz for GaAs tunnel-diode-loaded patch and from 56.694 GHz to 64.729 GHz for Ge tunnel-diode-loaded patch just by varying the bias voltage.